Respiratory Syncytial Virus Pneumonia in an Elderly Patient: A Case Report and Clinical Review - Eric Daniel Tenda; Almerveldy Azaria Dohong; Sahat Halim; Alfino Syahputra; Muhammad Aziz Arridho (Indonesia Journal of Chest Critical Emergency Medicine, 2026)
Background: Respiratory syncytial virus (RSV) is a major cause of acute lower respiratory tract infection and is increasingly recognized as a clinically significant cause of pneumonia in older adults. However, RSV remains underdiagnosed in adult pneumonia because clinical and radiologic features overlap with bacterial pneumonia and other viral infections, and RSV testing is not routinely performed. Case: A 91-year-old man presented with one day of cough, low-grade fever, reduced appetite, generalized weakness, and acute delirium. On admission, he was hemodynamically stable with oxygen saturation 97–98% on room air. Initial laboratory tests showed elevated C-reactive protein (20.7 mg/L), mild lymphopenia, microcytic anemia (hemoglobin 10.0 g/dL), and mild hyponatremia (sodium 132 mEq/L). Chest radiography revealed bilateral pulmonary infiltrates. A multiplex acute respiratory infection PCR panel detected RSV type A, while other respiratory viruses and atypical bacterial pathogens were negative. On day 3 of hospitalization, he developed acute hypoxemia (SpO₂ 86–88% on room air) accompanied by a marked rise in inflammatory markers (CRP peak 148 mg/L; procalcitonin 0.44 ng/mL). He improved with supplemental oxygen, intravenous methylprednisolone, and a macrolide antibiotic, and was discharged in stable condition on day 7. Discussion: This case highlights RSV as an important and often overlooked etiology of community-acquired pneumonia in very old patients, including atypical presentations such as delirium and late clinical deterioration after an initially stable course. Molecular diagnostics (PCR-based panels) can provide timely etiologic confirmation, support infection control measures, and guide antimicrobial stewardship, particularly when bacterial co-infection is uncertain. Conclusion: RSV should be considered in elderly patients with pneumonia, especially during periods of respiratory virus circulation. Early molecular testing may improve diagnostic accuracy and optimize clinical management and prevention strategies in high-risk older adults. Keyword: respiratory syncytial virus; pneumonia; elderly; multiplex PCR; case report